Original Research: Metabolic alterations from early life thyroxine replacement therapy in male Ames dwarf mice are transient. Issue 16 (October 2016) - Darcy, Justin; Fang, Yimin; Hill, Cristal M; McFadden, Sam; Sun, Liou Y; Bartke, Andrzej
Ames dwarf mice are exceptionally long-lived due to a Prop1 loss of function mutation resulting in deficiency of growth hormone, thyroid-stimulating hormone and prolactin. Deficiency in thyroid-stimulating hormone and growth hormone leads to greatly reduced levels of circulating thyroid hormones and insulin-like growth factor 1, as well as a reduction in insulin secretion. Early life growth hormone replacement therapy in Ames dwarf mice significantly shortens their longevity, while early life thyroxine (T4) replacement therapy does not. Possible mechanisms by which early life growth hormone replacement therapy shortens longevity include deleterious effects on glucose homeostasis and energy metabolism, which are long lasting. A mechanism explaining why early life T4 replacement therapy does not shorten longevity remains elusive. Here, we look for a possible explanation as to why early life T4 replacement therapy does not impact longevity of Ames dwarf mice. We found that early life T4 replacement therapy increased body weight and advanced the age of sexual maturation. We also find that early life T4 replacement therapy does not impact glucose tolerance or insulin sensitivity, and any deleterious effects on oxygen consumption, respiratory quotient and heat production are transient. Lastly, we find that early life T4 replacement therapy has long-lasting effects on bone mineral density and bone mineral content. We suggest that the transient effects on energy metabolism and lack of effects on glucose homeostasis are the reasons why there is no shortening of longevity after early life T4 replacement therapy in Ames dwarf mice.